Means of Controlling Urbanization- Certificate of Reconstruction Model- - Zebda , Noureddine (Journal of Social Sciences and Humanities, 2021)
One of the greatest developments that human civilizations have seen throughout the ages is urbanisation, that’s why man has created legal rules organizing it, and laws to regulate urban activity and guarantee individuals the rights to build their real estate. However, the building rights, in these laws, have not been left absolute, but are restricted by law with controls so as not to be in disorder, including the regulations made by the urban legislator in the field of reconstruction, the certificate of construction provided under the law 90/29 of 01/12/1990 which deals with the land-use and planning modified and complemented, as well as the executive decree 19/15 of January 25, 2015, which sets out how to prepare and deliver urbanisation contracts, and what is stated in the law 03/10 of 19/07/2003 on the protection of the environment in the context of sustainable development, rational management and the rational real estate wealth within the scope of preserving the environment in all its components poses the greatest challenge in the construction and expansion of cities. Therefore, the urban legislator has established legal and technical foundations to ensure the control of the construction process in a way that ensures the preservation of the environment as a natural medium that the human must preserve, according to the tools made by the legislator, which provide for the preparation of reconstruction. It also shows the right to be used to provide housing for the beneficiary, in accordance with legally licensed architectural conditions and standards that mainly take into account the conditions and requirements of protecting the environment from industrial and technological risks, or natural disasters within the framework of the requirements of sustainable development.